2012
DOI: 10.1002/jms.3073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sugars on liquid–vapour partition of volatile compounds in ready‐to‐drink coffee beverages

Abstract: The effect of sugars (sucrose, lactose, glucose, fructose, 10%w/v) on the liquid-vapour partition of selected volatile compounds of coffee beverages has been investigated in espresso coffee and ready-to-drink (RTD) canned coffee prepared and obtained by using the same Arabica roasted coffee beans blend. Aroma composition of coffee beverages has been preliminary investigated by headspace-gas chromatography (HS-GC) and solid phase microextraction-HS-GC-mass spectrometry to characterize the volatile pattern of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…The increase in volatile components could be due to the high concentration of each component (reflected in TSSC) cycle-by-cycle, which can be detected by the chromatograph. This effect is consistent with observed by Piccone et al [46] in coffee beverages, indicating that the concentration of sugars (such as sucrose, glucose, and fructose) positively affects the release of volatiles in the headspace. The volatile compounds concentrated by BCC are showed in the chromatograms.…”
Section: Profile Of Volatile Compoundssupporting
confidence: 92%
“…The increase in volatile components could be due to the high concentration of each component (reflected in TSSC) cycle-by-cycle, which can be detected by the chromatograph. This effect is consistent with observed by Piccone et al [46] in coffee beverages, indicating that the concentration of sugars (such as sucrose, glucose, and fructose) positively affects the release of volatiles in the headspace. The volatile compounds concentrated by BCC are showed in the chromatograms.…”
Section: Profile Of Volatile Compoundssupporting
confidence: 92%
“…The addition of sugar (polar cosolute) to the solution can modify the solubility of the volatile compound by favoring “salting‐in.” There is a change in the structure of the water around the less polar substance due to a change in the water solvency and/or by creating an intramolecular nonpolar environment for hydrophobic molecules to react with each other (solute interaction) (Chiou et al, ). The concentration of four selected aroma compounds significantly decreased when the sugar was increased from 0 to 10% wt/vol in a model system (Piccone, Lonzarich, Navarini, Fusella, & Pittia, ).…”
Section: Resultsmentioning
confidence: 99%
“…The influence of the addition of sugars on aroma release depends both on the aroma compound and the type of sugar studied. Glucose and sucrose present similar effects whereas lactose induces a greater increase in the release of aroma compounds (Piccone et al, 2012). By modelling aroma release as a function of sucrose concentration, Nahon et al (2000) observed that at low sucrose concentrations the partition coefficient primarily controls the flavour release, whereas at higher sucrose concentrations the mass transfer coefficient has more influence on their concentration.…”
Section: Effect Of Sugarmentioning
confidence: 98%